2018
DOI: 10.1128/aem.00991-18
|View full text |Cite|
|
Sign up to set email alerts
|

Substrate-Specific Differential Gene Expression and RNA Editing in the Brown Rot Fungus Fomitopsis pinicola

Abstract: Wood-decaying fungi tend to have characteristic substrate ranges that partly define their ecological niche. is a brown rot species of Polyporales that is reported on 82 species of softwoods and 42 species of hardwoods. We analyzed the gene expression levels and RNA editing profiles of from submerged cultures with ground wood powder (sampled at 5 days) or solid wood wafers (sampled at 10 and 30 days), using aspen, pine, and spruce substrates (aspen was used only in submerged cultures). expressed similar sets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 82 publications
(155 reference statements)
3
36
0
1
Order By: Relevance
“…Total RNA of samples from submerged culture was purified as described previously [29,31]. Plate-based RNA sample prep was performed on a PerkinElmer Sciclone NGS robotic liquid handling system (PerkinElmer, Inc., Waltham, MA) using the Illumina TruSeq Stranded mRNA HT sample prep kit utilizing poly-A selection of mRNA following the protocol outlined by Illumina in their user guide (Illumina, Inc., San Diego, CA).…”
Section: Rna Extraction and Library Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA of samples from submerged culture was purified as described previously [29,31]. Plate-based RNA sample prep was performed on a PerkinElmer Sciclone NGS robotic liquid handling system (PerkinElmer, Inc., Waltham, MA) using the Illumina TruSeq Stranded mRNA HT sample prep kit utilizing poly-A selection of mRNA following the protocol outlined by Illumina in their user guide (Illumina, Inc., San Diego, CA).…”
Section: Rna Extraction and Library Constructionmentioning
confidence: 99%
“…The latter study identified 8906 putative RNA editing sites, without significant bias among substitution types, but did not investigate conditionspecific RNA-editing events. We recently studied transcriptional regulation and RNA editing in the brown rot fungus Fomitopsis pinicola [29], showing that it is able to modify both transcription and RNA editing levels on different wood types in diverse genes encoding enzymes with known or potential function in wood decay (including laccase, benzoquinone reductase, aryl alcohol oxidase, cytochrome P450s, and various glycoside hydrolases).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous accumulation of oxalate indicated that Foma 4 persisted in the invasion mode until Km 10 was finally overgrown ( Table 1). The production of laccase ascribed to certain F. pinicola accessions [15,60,86] could not be recorded.…”
Section: Dynamics Of Interactionmentioning
confidence: 94%
“…In spite of a host range of 82 softwood and 42 hardwood spp. [15], the brown rot basidiomycete F. pinicola is not regarded as a serious pathogen in managed Eurasian forests due to its low and primarily hidden incidence in living trees. It is an important disease agent of wounded conifer spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation